Generasi Sandwich: Penyebab Stres Dan Pengaruhnya Terhadap Keputusan Keuangan - Nuryasman MN; Elizabeth Elizabeth (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
This research aims to find the correlation between financial literacy towards financial decision-making with retirement planning, sandwich generation, and stres as the mediating variables. Population used in this research is Indonesian people who are their productive age, are generating income, and are financially responsible for themselves and their families who are both older and younger than them. In this research, researchers gathered 382 samples dominated by people aged between 26 until 31 who live on Java Island. This research uses the quantitative method, cross-sectional, and convenience sampling using questionnaires distributed online. Then, the data is analyzed by using smartPLS 4.0 version. The result is financial literacy positively correlates with retirement planning; retirement planning positively influences sandwich generation; sandwich generation negatively affects stress, and stress negatively correlates with financial decision-making.